Facile fabrication and enhanced photoresponse of CuO/β-Ga2O3 nanostructure photodetector. (1st June 2022) - Du, Shiyu; Yu, Naisen; Wu, Yunfeng; Lin, Xiang; Liu, Benkang; Li, Haiou
Abstract: CuO/ β -Ga2 O3 hybrid structures with β -Ga2 O3 nanorods coated with CuO nanoparticle layers were successfully synthesized by a multi-cycle dipping and annealing process method. Compared with bare β -Ga2 O3 nanorods, the CuO/ β -Ga2 O3 hybrid structures had greatly enhanced and dramatically broadened responses to light in the range from the near-ultraviolet to visible light. This novel synthetic pathway will provide new possibilities to prepare nanomaterials that integrate oxide heterojunctions for photodetection applications.